Global perspectives on small and medium enterprises and strategic information systems : international approaches - Bharati, Pratyush, 1970-; Lee, In, 1958-; Chaudhury, Abhijit, 1958- (Hershey, PA : Business Science Reference, 2010)
'This book highlights the challenges faced by SMEs and how they are coping with the adverse environment through skillful use of IT and technologies such as Web 2.0, Enterprise Resource Planning (ERP), e-commerce, open source software, Business Process Digitization (BPD), and other emerging technologies'--Provided by publisher.
'Premier reference source.'--Cover.
Includes bibliographical references and index.
Keywords: Small business -- Management; Small business -- Information technology; Information technology -- Management